KARAKTERISTIK KOMPOSIT BIOPLASTIK GLUKOMANAN DAN MAIZENA DALAM PENGARUH VARIASI SUHU DAN WAKTU GELATINISASI - Indrawati, Cintia; Harsojuwono, Bambang Admadi; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): SeptemberDO - 10.24843/JRMA.2019.v07.i03.p14, 2019)
The aim of this study was to determine the effect of the temperature and time of gelatinization and its interactions on the composite characteristics of bioplastics glucomannan and cornstarch with to obtain gelatinization temperature and time to produce the best bioplastic glucomannan and cornstarch composites. This study used factorial randomized block design. Factor 1 gelatinization temperature consisting of 3 levels, namely 70 ± 1; 75 ± 1; 80 ± 1°C. Factor 2 is gelatinization time, for 2, 3 and 4 minutes. Variables observed included tensile strength, elongation at break, young modulus, swelling, biodegradation and functional group profile. The data were analyzed for diversity and continued with the BNJ test. The results showed that the temperature and time of gelatinization and their interactions had a very significant effect on tensile strength and elasticity. The temperature and time of gelatinization had a very significant effect but did not interact with elongation and did not significantly affect the swelling and biodegradation of bioplastic composites. The best bioplastic glucomannan and maizene composites were at a temperature treatment of 80 ± 1°C and 4 minutes gelatinization time with tensile strength characteristics (3.390 mpa); elasticity (35.811 mpa); elongation at break (12.3%); swelling (68.13%); degradation time of 8 days and contains hydroxyl (O–H) functional groups, alkene (C– H), carboxyl (C–O), carbonyl (C=O) and alkyne (C?C). Keywords : Composites bioplastic, glucomannan, maizena, temperature and time of gelatinization